AN UPDATED SYNOPSIS OF LUDWIGIA (ONAGRACEAE) IN MALESIA - Ian Turner (REINWARDTIA, 2021)
TURNER, I. M. 2021. An updated synopsis of Ludwigia (Onagraceae) in Malesia. Reinwardtia 20(1): 9–16. — A synopsis of the seven native or naturalised species of Ludwigia  (Onagraceae) occurring in Malesia is presented. The newly  established Ludwigia  leptocarpa  is  included.  The  paper  incorporates  a  key  to  the  species, synonymy  and typification. Lectotypes are designated for 25 names, including five at the second step.